1993
DOI: 10.3109/00016359309040587
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of damage to removable dentures in two cities in Finland

Abstract: The number of damaged dentures and type of damage to removable dentures repaired in dental laboratories was investigated using a questionnaire sent to 24 dental laboratories in Finland. Eight variables were examined for each damaged denture. The results showed that the type of dentures most commonly needing repair was the complete upper denture (49%). The most frequent type of damage was breakdown of the acrylic base and loosening of an artificial tooth. The chi-square test established a statistical dependence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
55
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(56 citation statements)
references
References 10 publications
1
55
0
Order By: Relevance
“…Vallittu et al 4 noted that the highest incidence of denture fractures occurred between 16-36 months after being in service.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vallittu et al 4 noted that the highest incidence of denture fractures occurred between 16-36 months after being in service.…”
Section: Introductionmentioning
confidence: 99%
“…Farmer 3 listed various clinical factors such as improperly contoured mandibular occlusal plane, high frenal attachment, incorrect occlusal schemes, heavy occlusal forces, poor adaptation of the denture base to the residual alveolar ridge and denture base thickness as primary causes of denture fractures. Vallittu et al 4 noted that the highest incidence of denture fractures occurred between 16-36 months after being in service.The clinician must often decide whether to repair or replace the broken denture . To minimize inconvenience to the patient and save costs in the reconstruction of the dentures, quick and reliable denture repairs are often necessary.…”
mentioning
confidence: 99%
“…One study 3 reported that midline fractures generally begin either at the labial notch or in the anterior part of the denture palate. Another study 2 also reported that a midline fracture of a maxillary complete denture ran through the notch between the two central teeth, extending partially or completely through the denture base.…”
Section: Introductionmentioning
confidence: 99%
“…The most frequently damaged denture is the maxillary complete denture. Fracture of the acrylic base was found in many damaged maxillary complete dentures; typically, the fatigue failure of maxillary complete dentures is a midline fracture 2 . One study 3 reported that midline fractures generally begin either at the labial notch or in the anterior part of the denture palate.…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies reported that the fracture rate of acrylic resin was 64% [8] and 68% [9]. Dentures fracture may occur inside or outside the mouth due to expelling the denture from the mouth while coughing, or simply dropping it [10].…”
Section: Introductionmentioning
confidence: 99%